Using the SNA and SAMs for a better (socio-)economic modelling - Santos, Susana (2016)
The Social Accounting Matrix (SAM) can be considered a tool to be used for measuring a society’s activity. It provides a description of that activity, which can be either empirical or theoretical, depending on whether it is presented in a numerical or an algebraic version, respectively. Special attention will be paid here to the numerical version, and a method will be proposed for its construction from the United Nations System of National Accounts (SNA). After the first and most fundamental contribution made by Richard Stone, the SNA (with its successive improved versions, from 1953 to 2008) has established a set of rules for measuring a society’s activity, which the statistical offices of countries or groups of countries have adopted and adapted to their specific realities, thus defining their own systems. Through an application of the SAM to Portugal, a basic structure, based on the SNA, will be proposed for this matrix, and its consistency within the whole system will be studied. Possible disaggregations, extensions, aggregates, indicators and balances will be calculated and other aspects beyond that basic structure will also be examined. It will be concluded that using the SNA in a SAM-based approach contributes towards a better modelling of (socio-)economic policy, emphasizing the importance of that approach as a valuable support in policy decision processes.